‘Haemodialysis burden’ overweighs the associations of demographic, social and clinical factors on quality of life: a single centre study from Pakistan - Saleem, Imran; Dhrolia, Murtaza; Qureshi, Ruqaya; Nasir, Kiran; Ahmad, Aasim (Journal of the Pakistan Medical Association, 2022)
Objective: To assess health-related quality of life in haemodialysis patients, and the impact of various factors in this regard. Method: The retrospective observational cross-sectional study was conducted at The Kidney Centre Post-Graduate Training Institute, Karachi, and comprised data from June to December 2019 of patients on maintenance haemodialysis. The health-related quality of life was assessed using the self-administered Urdu version of the Kidney Disease Quality of Life-Short Form version 1.3. Data was analysed using SPSS 21. Results: Of the 150 questionnaires distributed, 110(73.3%) were received fully completed. There were 64(58.2%) males, 46(41.8%) were females, 90(81.8%) were under aged <60 years, 76(69%) were married, 54(49.1%) had income up to PKR50,000, 64(58.2%) had received education up to secondary school, and 56(50.9%) had been on haemodialysis for <5 years. The overall health-related quality of life mean score was 52.0±11.7, and it had no significant association with age, gender, haemodialysis duration, marital status, education level, and income of the subjects (p>0.05). Conclusion: The health-related quality of life in haemodialysis patients was not found to have significant association with age, gender, haemodialysis duration, marital status, education level, and income. Key Words: Quality of life, Haemodialysis, Kidney disease.